Combination therapy utilizing ketamine and transcranial magnetic stimulation for treatment-resistant depression: a case report. (4th March 2015) - Best, Steven Richard Devore; Griffin, Brian
<x xml:space="preserve">Abstract</x> In the present article, we report on the case of a 23-year-old woman with a history of treatment-resistant depression who achieved significant symptom improvement with a novel treatment consisting of ketamine, a dissociative anesthetic, and external neuromodulation with transcranial magnetic stimulation (TMS). This case highlights the need for further investigation of treatments pairing external neuromodulation with dissociative anesthetics.